Review of the Fund's Income Position for FY 2009 and FY 2010. (Policy Papers; Policy Paper, 2009)
This paper reviews the Fund's income position for FY 2009 and FY 2010. The proposals build on previous discussions relating to implementation of the new income model, the framework for accumulating precautionary balances, and the recent reform of the Fund's lending toolkit. The paper is structured as follows: Section II reviews the income position for FY 2009 and explains the main changes from the projections at the midyear review; Section III makes proposals that pertain to the FY 2009 income position, including the disposition of investment income, the overall income position of the General Resources Account (GRA), and the annual reimbursement of the GRA for the expenses of conducting the business of the SDR Department and the MDRI-I Trust; Section IV reviews the FY 2010 income outlook, including the margin for the rate of charge; Section V reviews the burden sharing mechanism; and Section VI reviews special charges.